Pseudohypoxic stabilization of HIF1α via cyclophilin D suppression promotes melanoma metastasis - Hye-Kyung Park; Sung Hu; So Yeon Kim; Sora Yoon; Nam Gu Yoon; Ji Hye Lee; Wonyoung Choi; Sun-Young Kong; Jong Heon Kim; Dougu Nam; Byoung Heon Kang (Signal Transduction and Targeted Therapy)
Abstract Stabilization of hypoxia-inducible factor 1 alpha (HIF1α), which plays a pivotal role in regulating cellular responses to insufficient oxygen, is implicated in cancer progression, particularly epithelial-mesenchymal transition and metastatic dissemination. Despite its crucial role in tumorigenesis, the precise mechanisms governing HIF1α stabilization under varying tumor microenvironmental conditions are not fully understood. In this study, we show that stabilization of HIF1α in metastasizing melanoma under mild hypoxia is regulated primarily by mitochondrial reactive oxygen species (ROS) rather than by reduced oxygen levels. Activated HIF1α suppresses the expression of cyclophilin D (CypD), a regulator of the mitochondrial permeability transition pore (mPTP), as a reciprocal regulatory mechanism to sustain HIF1 signaling via upregulation of microRNAs miR-23a and miR-27a. Reduced expression of CypD leads to mPTP closure, resulting in elevated mitochondrial calcium accumulation and enhanced oxidative phosphorylation, which in turn increases mitochondrial ROS levels. The ROS then inhibits a prolyl hydroxylase, establishing a pseudohypoxic state that stabilizes HIF1α even in the presence of oxygen. This HIF1-reinforced and mitochondria-driven pseudohypoxic induction is essential for maintaining HIF1 signaling under conditions of mild hypoxia or transient increases in oxygen levels during melanoma metastasis. Overexpression of CypD reversed the pseudohypoxic state and potently inhibited melanoma metastasis. Thus, mitochondria-driven pseudohypoxic induction is critical for sustaining HIF1 signaling in metastasizing cancer cells and can be exploited to develop anti-metastatic therapies.